(:unas) unassigned - Nyongesa, Catherine (My University, 2006)
A phase I dose escalation study of Cisplatin chemotherapy in patients with carcinoma of the cervix receiving pelvic radiotherapy PATIENTS WITH CARCINOMA OF THE CERVIX RECEIVING PELVIC RADIOTHERAPY.
0300009Y Masters Dissertation (Faculty of Health Sciences)
Keywords: PATIENTS; CARCINOMA; CERVIX; RADIOTHERAPY